Oesophageal Doppler guided optimization of cardiac output does not increase visceral microvascular blood flow in healthy volunteers - Heinink, Thomas P.; Read, David J.; Mitchell, William K.; Bhalla, Ashish; Lund, Jonathan N.; Phillips, Bethan E.; Williams, John P. (Wiley, 2017)
Background